2017
DOI: 10.1186/s12864-017-3939-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensory genes in the antennal transcriptome of two syrphid species, Episyrphus balteatus and Eupeodes corollae (Diptera: Syrphidae)

Abstract: BackgroundPredatory syrphid larvae are an important natural enemy of aphids in cotton agro-ecosystems in China. Their behaviors in prey foraging, localization and oviposition greatly rely on the perception of chemical cues. As a first step to better understand syrphid olfaction at the molecular level, we have performed a systematic identification of their major chemosensory genes.ResultsMale and female antennal transcriptomes of Episyrphus balteatus and Eupeodes corollae were sequenced and assembled using Illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
80
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(89 citation statements)
references
References 104 publications
(161 reference statements)
7
80
2
Order By: Relevance
“…In consistent with several previous reports Wang, Liu, et al, 2017;Wang, Li, et al, 2017), the results of C-pattern analysis (Supporting Information Figures S4-S6) and motif pattern ( Figure 3) suggested that CSPs are more conservative than OBPs.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In consistent with several previous reports Wang, Liu, et al, 2017;Wang, Li, et al, 2017), the results of C-pattern analysis (Supporting Information Figures S4-S6) and motif pattern ( Figure 3) suggested that CSPs are more conservative than OBPs.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, according to the results of MEME motif analysis, both EonuOBPs and EounCSPs presented several different motif patterns, with the most common one being 1‐3‐5‐2 and 3‐6‐2‐5‐1‐7‐4‐8, respectively. In consistent with several previous reports (Gu et al., ; Wang, Liu, et al., ; Wang, Li, et al., ), the results of C‐pattern analysis (Supporting Information Figures S4–S6) and motif pattern (Figure ) suggested that CSPs are more conservative than OBPs.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations